Anton Pannekoek: Ways of Viewing Science and Society - Tai, Chaokang; van der Steen, Bart; van Dongen, Jeroen (Studies in the History of Knowledge, 2019)
Anton Pannekoek (1873-1960), prominent astronomer and world-renowned socialist theorist, stood at the nexus of the revolutions in politics, science and the arts of the early twentieth century. His astronomy was uniquely visual and highly innovative, while his politics were radical. Anton Pannekoek: Ways of Viewing Science and Society collects essays on Pannekoek and his contemporaries at the crossroads of political history, the history of science and art history.